Schools and juvenile justice - Fine, Adam D. (The Oxford handbook of developmental psychology and the law, 2024)
School environments prioritize not just academic achievement but also youth development and socialization. However, the school environment can serve as a catalyst for involving youth in the juvenile justice system. In contemporary schools, students often have contact with legal actors, such as school resource officers or probation officers. Many schools also invest in policies and programs that involve bringing court actors into the school environment to respond to student misbehavior or to be a part of efforts to improve school safety. This chapter discusses the current state of the literature on how schools and the legal system interact, and their combined impact on students’ well-being. Scholars have found that embedding legal actors within schools can disproportionately affect minority students and create a school-to-prison pipeline. Simultaneously, there is little evidence that these initiatives have improved school safety. It concludes with recommendations for advancing research, policy, and practice.